The Ambivalent Role of Technology on Human Relationships: An Afrocentric Exploration - Sophia Chirongoma; Lucia Mutsvedu (Palgrave Macmillan, Cham, 2022)
Whilst using modern communication technology has immensely aided in connecting people, communities and nations as well as facilitating smooth global interactions, however, its abuse can also have far-reaching repercussions. For instance, there have been escalating reports of cyberbullying, cyber terrorism and numerous forms of cybercrimes, especially in the economic sector. Some extremist ethnic, religious and social groups have also manipulated the cyberspace to pursue their own selfish agendas. Conversely, technology has become a formidable tool in connecting families and friends as well as assisting in conducting business transactions at a much faster and convenient pace. Tapping into the rights-based theory and the African ethic of Ubuntu/Unhu, our chapter underscores how communication technology can either enhance or infringe upon human relations in our contemporary times. The first part reflects on how technology can positively contribute towards cementing human relationships. The second part discusses how the abuse of technology can impact negatively on the human rights and dignity of others. The concluding section proffers how the African ethic of Ubuntu/Unhu can foster principles that will help us to become responsible citizens of the world and enhance our capacity to make the best use of technology.